Effects of alkali treatment on tannins and phytates in red sorghum, white sorghum and pearl millet - Ochanda, S. O.; Onyango, C. A.; Mwasaru, M. A.; Ochieng, J. K.; Mathooko, F. M. (www.biosciences.elewa.org, 2010)
Objective:Tannins and phytates anti-nutrients are abundant in sorghum and millet; they reduce the nutrient value and organoleptic properties of foods. Alkali treatment was therefore employed to detoxify them. Methodology and results:Grain samples were sourced from the selected site (Nguni, Ukambani Kenya). Preliminary physical and chemical analysis were carried out to determine the indicators of ant-nutrients (colour and presence of testa) followed by actual l evels of anti-nutrients (quantities of tannins and phytates) and the suitability of the grains for use in other treatments like germination which are normally employed in the utilization of the cereals (Shull et al., 1987). Following the physical and chemical analysis, alkali treatment was done to reduce the levels of the anti-nutrients and the most effective alkali identified. The quantities of the alkali application was based on aconcentration that retained germinability of the grains, had no negative effect on consumer acceptability and had acceptable residual values of any potentially harmful chemical on the grains. Four alkalis were used including ash from pigeon pea pods, magadi soda,ammonia and sodium bicarbonate. The cereals were steeped in the alkali solutions of varying concentrations from 0-10% at varying time periods of between 0-7days. The reduction in tannins and phytates were analyzed. The overall best alkali was magadi soda applied at 1% for 2 days of steeping, this reduced tannins and phytates by 68-75% and 14-29%, respectively. The grains had acceptable organoleptic properties, over 91% germinability andthe residual value of sodium from the magadi soda was 98.09 mg/100g which was acceptable (Shull et al., 1987; Makokha et al., 2002). Conclusion and application of results:The different alkalis proved effective in the detoxification of tannins and phytates, each of them reducing statistically significant amounts of the anti-nutrients (p≤0.05). The most effective of them was magadi soda, followed byash, ammonia and sodium bicarbonate. This information is useful to the communities using these cereals since they can use locally available compounds like magadi soda and ash from the legumes they use to remove the anti-nutrients associated with the cereals thus improving their quality and nutritive value. If the alkalis are used in the right quantities as shown in this study, germinability of the grains and organoleptic properties can still be retained. Therefore alkali treatment can be used in combination with other processing techniques like malting and even fermentation to add value to sorghum and millet. Key words: Tannins, phytates, detoxification, alkali treatment